Dopamine and glutamate receptors control social stress-induced striatal ERK1/2 activation. (1st June 2021) - Contesse, Thomas; Broussot, Loïc; Fofo, Hugo; Vanhoutte, Peter; Fernandez, Sebastian P.; Barik, Jacques
Abstract: Stress has been acknowledged as one of the main risk factors for the onset of psychiatric disorders. Social stress is the most common type of stressor encountered in our daily lives. Uncovering the molecular determinants of the effect of stress on the brain would help understanding the complex maladaptations that contribute to pathological stress-related mental states. We examined molecular changes in the reward system following social defeat stress in mice, as increasing evidence implicates this system in sensing stressful stimuli. Following acute or chronic social defeat stress, the activation (i.e. phosphorylation) of extracellular signal-regulated kinases ERK1 and ERK2 (pERK1/2), markers of synaptic plasticity, was monitored in sub-regions of the reward system. We employed pharmacological antagonists and inhibitory DREADD to dissect the sequence of events controlling pERK1/2 dynamics. The nucleus accumbens (NAc) showed marked increases in pERK1/2 following both acute and chronic social stress compared to the dorsal striatum. Increases in pERK1/2 required dopamine D1 receptors and GluN2B-containing NMDA receptors. Paraventricular thalamic glutamatergic inputs to the NAc are required for social stress-induced pERK1/2. The molecular adaptations identified here could contribute to the long-lasting impact of stress on the brain and may be targeted to counteract stress-related psychopathologies. Highlights: Social stress activates striatal ERK1/2 in the nucleus accumbens (NAc). Antagonism of dopamine D1. R prevents stress-induced ERK1/2 activation in the NAc. Blocking NMDA GluN2A or GluN2B receptors prevents activation of ERK1/2 by stress in the NAc. Pharmacogenetic silencing of paraventricular thalamic inputs to the NAc reduces stress impact.